High Temperature Adaptation Mechanisms of Common Carp (Cyprinus carpio) in Globally Important Agricultural Heritage System - Xiangbing Cheng; Ziyi Chen; Fangcheng Li; Qigen Liu; Wenjing Hu; Jiamin Sun (Marine Biotechnology, 2026)

Game-based event-triggered path-following optimal control of unmanned sailboats in sensor-to-controller channel - Yingjie Deng; Fangcheng Liu; Yifei Xu; Le Chen; Fubo Li; Jing Yan (Ocean Engineering, 2026)

A novel composite building envelope integrating phase change material gypsum boards and gravity heat pipes: experimental and numerical investigation - Nian Zhu; Fan Li; Xin Wang; Hongxia Chen; Fangcheng Kou (Journal of Cleaner Production, 2026)

Spatiotemporal characteristics and meteorological drivers of background ozone in China's Pearl River Delta region - Xiaoyong Liu; Jun Yan; Fangcheng Su; Hongrui Li; Wei Wei; Hui Gao; Junhui Yan (Atmospheric Pollution Research, 2026)

From digestion to delivery: the gastrointestinal fate and functional duality of goat milk-derived extracellular vesicles - Chunping Chen; Cong Zheng; Fangcheng Hu; Yue Li; Xingyuan Liu; Wenxu Zhou; Baolong Liu; Lin Han; Caian He; Min Wang (Food Chemistry, 2026)

Intrinsic nitrogen-doped graphdiyne boosts sodium storage via fast ion desolvation kinetics - Hao Huang; Fangcheng Qiu; Ze Yang; Yan Xu; Xiao Lu; Xiaodong Li; Huiping Du; Zhufeng Hou; Changshui Huang (Chemical Engineering Journal, 2026)

Corrigendum to “Identification and in vitro anti-inflammatory activity of different forms of phenolic compounds in Camellia oleifera oil” [Food Chem. 344 (2021) 128660] - Tao Zhang; Fangcheng Qiu; Li Chen; Ruijie Liu; Ming Chang; Xingguo Wang (Food Chemistry, 2025)

Effects of exhalation directions on particle dispersion in high-speed train cabin and seat allocation strategies: an experimental and numerical study - Hang Zhang; Tiantian Wang; Yaozheng Zeng; Hengkui Li; Yan Zhu; Fangcheng Shi; Yu Wang; Yibin Lu; Jianfeng Zhou (Building and Environment, 2025)

High resolution residential emission inventory and relationships between urban residential emissions and incomes in megacity Zhengzhou, China - Fangcheng Su; Yuan Li; Qixiang Xu; Xiao Li; Panpan Liu; Bingnan Zhao; Ke Wang; Ruiqin Zhang (Environmental Pollution, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

The importance of interface interactions in flexible sensing materials: classification, effect, and application - Fei Chen; Fangcheng Qiu; Xiucun Li; Yufeng Song; Xiao Liu; Hong Jiang; Hongbin Liu; Yonghao Xiao; Meng Gao; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2025)

An efficient thermal comfort prediction method for indoor airflow environment using a CFD-based deep learning model - Tiantian Wang; Xiaoying Li; Yibin Lu; Lini Dong; Fangcheng Shi; Zhang Lin (Building and Environment, 2025)

Epigenetic Resources: Gaps in Aquatic Animal Germplasm Research - Fangcheng Li; Junfang Zhang; Xiangbing Cheng; Xinyao Cui; Jiamin Sun; Qigen Liu (Reviews in Aquaculture, 2025)
Aquatic animal germplasm research plays a vital role in biodiversity conservation and sustainable aquaculture. The traditional view is that diversity of germplasm resources is commonly attributed to genetic variation. However, recent studies in transgenerational epigenetics have shown that epigenetic information can also be passed down to offspring, which is consistent with the definition of germplasm. Therefore, it is necessary to define epigenetic information, such as DNA methylation, histone modifications, and ncRNAs, which can be passed down through generations, as epigenetic resources and incorporate them into the concept of germplasm. Germplasm resources should include not only genetic resources but also epigenetic resources. Epigenetic variation can arise from genetic, environmental, or stochastic factors. Genetic and epigenetic variation co‐determine phenotypic traits. It has been demonstrated that epigenetic information can be inherited across generations in aquatic animals. DNA methylation, histone modification, and ncRNAs are involved in addressing environmental challenges, maintaining genetic diversity, improving breeding strategies, combating inbreeding decline, and age determination. Therefore, future research on epigenetic resources is important for germplasm conservation, development, and utilization. This review proposes a new theoretical framework to elucidate the place of epigenetic resources in germplasm research and collects articles from the past 8 years that explore the inheritance of epigenetic information in aquatic animals. Integrating epigenetic research into germplasm studies enhances our understanding of population dynamics, adaptation, and evolutionary processes, thereby informing conservation strategies and enhancing aquaculture practices. By considering both genetic and epigenetic resources, we can address the challenges facing germplasm diversity and sustainable aquaculture more comprehensively.

Long-term evolution of carbonaceous aerosols in PM2.5 during over a decade of atmospheric pollution outbreaks and control in polluted central China - Zhe Dong; Xiao Li; Zhangsen Dong; Fangcheng Su; Shenbo Wang; Luqi Shang; Zihan Kong; Shanshan Wang (Science of The Total Environment, 2024)

Tetramethylpyrazine Nitrone Promotes the Clearance of Alpha-Synuclein via Nrf2-Mediated Ubiquitin–Proteasome System Activation - Baojian Guo; Chengyou Zheng; Jie Cao; Xiaoling Qiu; Fangcheng Luo; Haitao Li; Simon Mingyuan Lee; Xifei Yang; Gaoxiao Zhang; Yewei Sun; Zaijun Zhang; Yuqiang Wang (NeuroMolecular Medicine, 2024)

Transcriptome analysis in gill reveals the adaptive mechanism of domesticated common carp to the high temperature in shallow rice paddies - Xiangbing Cheng; Fangcheng Li; Junjie Lu; Yuanlin Wen; Zhili Li; Jiayi Liao; Jiangwei Cao; Xumeng He; Jiamin Sun; Qigen Liu (Aquaculture, 2024)

Molecular-scale investigation on the composition, sources and secondary generation of organic aerosols in polluted central China - Zhe Dong; Xiao Li; Fangcheng Su; Zihan Kong; Luqi Shang; Zihan Li; Ruiqin Zhang (Journal of Cleaner Production, 2024)

Surrogate modelling of the high-static-pressure fan for high-speed trains and its dynamic airtightness analysis using CFD - Yibin Lu; Tiantian Wang; Xiaohui Xiong; Hengkui Li; Fangcheng Shi; Chen Jiang (Building and Environment, 2024)

Effects of impure ions in precursors on the formation of active oxygen in MnO2 for promoting VOCs oxidation - Juexiu Li; Tonglu Lu; Changsen Zhang; Fangcheng Su; Bo Shen; Lizhong Liu; Panpan Liu (Process Safety and Environmental Protection, 2023)

Numerical study of the effect of composition models on cough droplet propagation distributions in confined space - Tiantian Wang; Fushan Shi; Fangcheng Shi; Chunhui Li; Lei Zhang; Jiabin Wang; Chen Jiang; Bosen Qian; Lei Dai; Peng Ji (Building and Environment, 2023)

RNA-Seq Reveals the Effect of Ethylene on the Volatile Organic Components (VOCs) of Cavendish Banana at Different Post-harvesting Stages - Tongxin Dou; Chunhua Hu; Shujing Zhao; Huijun Gao; Weidi He; Guiming Deng; Ou Sheng; Fangcheng Bi; Qiaosong Yang; Chunyu Li; Ganjun Yi; Tao Dong (Journal of Plant Growth Regulation, 2022)
Aroma serves as one of the decisive factors influencing the value of banana commodities. Most of characteristic volatile organic components (VOCs) are formed during post-harvesting. However, the changing of VOCs of banana at different post-harvesting stages remain ambiguous. In this study, the VOCs of Cavendish banana for the four typical post-harvesting stages (green stage/half of yellow stage/yellow ripening stage/over ripening stage) are clarified using headspace solid phase micro-extraction (HS-SPME), combined with gas chromatography-mass spectrometry (GC–MS). The results inferred that the relative content of branched-chain esters such as acetate and butyrate, which form the main contributors of aroma in bananas, is higher in the T2 and T3 stages. Further, RNA-Seq technology was employed to clarify the formation mechanism of banana aroma in the post-harvesting stage. The MaTGL4 gene of the linoleic acid metabolism pathway and the MaBCAT3 and MaBCAT5 genes of the valine, leucine and isoleucine degradation pathway in banana suggest the expression is active late in the ripening stage, and the upregulated expression of these genes is analogous to the formation of aroma components such as branched-chain esters and hexenal. The above results not only provide baseline data on the differences in physical and chemical properties of VOCs in various post-harvesting stages of banana production, but also provide theoretical guidance facilitating the subsequent improvement of the commercial value of bananas through genetic improvement.

Dietary inflammatory index and risk of colorectal adenoma: effect measure modification by race, nonsteroidal anti-inflammatory drugs, cigarette smoking and body mass index? - Fangcheng Yuan; Lin Deng; Xiangqing Sun; Zhengyi Chen; Nitin Shivappa; Ashutosh K. Sheth; Gregory S. Cooper; James R. Hebert; Li Li (Cancer Causes & Control, 2021)

Bare surface soil moisture retrieval from the synergistic use of optical and thermal infrared data - Pei Leng; Xiaoning Song; Zhao-Liang Li; Jianwei Ma; Fangcheng Zhou; Shuang Li (International Journal of Remote Sensing, 2014)